2023
DOI: 10.3390/ijms24087569
|View full text |Cite
|
Sign up to set email alerts
|

Linderone Isolated from Lindera erythrocarpa Exerts Antioxidant and Anti-Neuroinflammatory Effects via NF-κB and Nrf2 Pathways in BV2 and HT22 Cells

Abstract: Linderone is a major compound in Lindera erythrocarpa and exhibits anti-inflammatory effects in BV2 cells. This study investigated the neuroprotective effects and mechanisms of linderone action in BV2 and HT22 cells. Linderone suppressed lipopolysaccharide (LPS)-induced inducible nitric oxide synthase, cyclooxygenase-2, and pro-inflammatory cytokines (e.g., tumor necrosis factor alpha, interleukin-6, and prostaglandin E-2) in BV2 cells. Linderone treatment also inhibited the LPS-induced activation of p65 nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The results show that only compounds 7 (dihydropashanone) and 13 (linderone) exhibited neuroprotective effects in the neural cells. Previous studies have demonstrated the anti-neuroinflammatory effects of linderone [ 18 ]. Therefore, we chose to focus on dihydropashanone for this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results show that only compounds 7 (dihydropashanone) and 13 (linderone) exhibited neuroprotective effects in the neural cells. Previous studies have demonstrated the anti-neuroinflammatory effects of linderone [ 18 ]. Therefore, we chose to focus on dihydropashanone for this study.…”
Section: Discussionmentioning
confidence: 99%
“…In our earlier study, 18 compounds were identified in L. erythrocarpa , including dihydropashanone [ 17 ]. Dihydropashanone was found to inhibit the excessive production of LPS-induced NO in both BV2 and RAW264.7 cells [ 18 ]. However, dihydropashanone has only been confirmed to inhibit NO production in BV2 cells [ 18 ] and no additional mechanistic studies related to inflammation regulation have been conducted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, these two products have not been found in any other plants. They bear a structural similarity to the anti-neuroinflammatory agent linderone, a cyclo-pentenedione from Lindera erythrocarpa [ 92 ]. The related furanone derivative designated fissohamione ( 70 ) has also been found in F. oldhamii seed extract, but its bioactivity, if any, is unknown at present ( Figure 5 ) [ 27 ].…”
Section: Phytochemical Content Of Fissistigma Oldhamiimentioning
confidence: 99%
“…To our knowledge, these two products have not been found in any other plants. They bear a structural similarity to the anti-neuroinflammatory agent linderone, a cyclo-pentenedione from Lindera erythrocarpa [92]. The related furanone derivative designated fissohamione Two main steroids were identified in the methanolic fruit extract: β-sitosterol (64) (cupreol) and a glucoside derivative (65) [25,86].…”
Section: Natural Products From the Seedsmentioning
confidence: 99%